Evaluation of anti-asthmatic and anti-cholinergic activity of ethanolic extract of Tectina grandis Linn. bark - Jaybhaye, Deepali J.; Chaudhary, Prashant S.; Chandra, Shruti; Johar, Sukhmeen (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Asthma is a chronic disease that affects approximately 300 million people worldwide. Tectona grandis Linn. bark, also known as Teak (English), is traditionally used to treat asthma. However, the scientific data on anti-asthmatic and anti-cholinergic of this plant has got little attention. An attempt has been based on ethanolic extract of bark of Tectona grandis Linn. shown a tremendous effect on asthma when comparative study was done with normal and treated group. Methods: The anti-asthmatic activity of a 95% ethanol and 5% distilled water extract of dried and fresh Tectona grandis Linn. bark, was evaluated against histamine and acetylcholine-induced preconvulsive dyspnea (PCD) in guinea pigs fasted for 24 h were exposed to an atomized fine mist of 2% histamine dihydrochloride and acetylcholine aerosol (dissolved in normal saline) using nebulizer at a pressure of 300 mmHg in the histamine chamber (24×14×24 cm, made of perplex glass. They were divided in groups Mepyramin (8 mg/kg) intraperitonially, atropine aerosol and Tectona grandis bark formulation (2.5, 5, 10 gm/kg) were administered orally 30 min prior to exposure. Animals, which did not develop typical asthma within 6 minutes, were taken as protected. Results: Ethanolic extract of Tectona grandis Linn. bark at 5 and 10 gm/kg significantly reduce bronchoconstriction as compared to control group along with significant mast cell stabilization activity. Conclusions: In conclusion, the present study shows that the ethanolic bark extract of Tectona grandis Linn. has potential antiasthamatic and antichlolinergic action in histamine and acetylcholine broncocontraction in guinea pigs.